Music technology 101 - Jones, Heath (Milwaukee, WI Hal Leonard, 2021)
Ideal for students and teachers, this book breaks down the basics of music creation in the technology lab or at home using a digital audio workstation
Keywords: Sonido -- Grabación y reproducción digital; Música -- Estudio y enseñanza